Pengaruh Kombinasi Zeolit, Serbuk Gergaji, dan Pasir sebagai Media Tumbuh Rumput Bermuda (Cynodon dactylon Cv. Tiffdwarf) terhadap Kualitas Fungsionalnya - Nizar Nasrullah; Kgs. Azhar Ansari (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2000)
The objective of the study is to investigate the effect of the mixture of sow dust, zeolit, and sand as media on turf qualities of Bermuda Grass (Cynodon dactylon var. Tiffdwarf). There are 6 treatments of planting media including : sand 100%, sand 75 % + saw dust 25 % + zeolit 0 %, sand 50 % + sow dust 50 % + zeolit 0 %, sand 50 % + sow dust 25 % + zeolit 25 %, and sand 50 % + sow dust 0 % + zeolit 50 %. The treatment have 3 replication ang arranged in Randomized Block Design. Analysis of media show the addition of sow dust 25 - 50 % into sand media increased physical qualities of media including the increasing of the water content of media and decreased bulk density of the media. The addition of sow dust 25 % into sand media perform the best qualities of turf compared to the other media including of dry weight of shoots, density of shoot, height of shoot, length of root and the shoot - root ratio.